Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Minuman Herbal Instan Sebagai Upaya Meningkatkan Ekonomi Warga - Pertiwi, Novia Ayu Sekar; Nasrulloh, Basharudin; Wilujeng, Febri Tri; Azam, Mohammad Choirul; Sari, Nila Bunga (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The training program on making instant herbal drinks in Dukuhdimoro Village aims to address unpredictable weather conditions and enhance the economic status of PKK mothers. Conducted through the Service-Learning method, it involves PKK mothers as participants learning to produce herbal drinks that are more durable and have higher economic value. Evaluation is conducted through participant engagement, speaker qualifications, feedback, direct impacts, and resource availability. Results indicate an improvement in participants' knowledge and skills, along with positive economic and social impacts on Dukuhdimoro Village. The training provides innovation in local agricultural processing, elevating product value and serving as an economic booster. As a sustainable initiative, it fosters creativity and innovation among PKK mothers and equips them with skills for the future. Thus, the program not only enhances economic prosperity but also strengthens the local community's ability to utilize natural resources sustainably.